Genetic variants in apoptosis-related genes associated with colorectal hyperplasia - Gerola, Stefano; Nittka, Stefanie; Kähler, Georg; Tao, Sha; Brenner, Hermann; Binelli, Giorgio; Eils, Roland; Brors, Benedikt; Neumaier, Michael (Genes, chromosomes & cancer, 2014)
Deregulation of apoptosis is a frequent alteration in early benign lesions of the colon mucosa and is thought to be a major contributor to tumor progression and cancer. Single nucleotide polymorphisms (SNPs) within apoptosis-related genes could affect apoptotic responses and their identification might provide a basis to assess individual risk for development of early lesions. To investigate a possible association between genetic polymorphisms and the occurrence of hyperplastic polyps (HP), we developed a custom DNA chip assay for 1,536 SNPs in the coding and flanking regions of 826 genes with known functional roles in apoptosis or apoptosis-associated (e.g., stress-related) pathways. During a first round of screening, genotypes were determined for 272 endoscopy patients harboring hyperplastic colorectal polyps and for 512 sex and aged-matched controls. A set of 14 candidate SNPs associated with HP (P < 0.01) was then evaluated in an independent cohort of patients (n = 38) and controls (n = 38). Following meta-analysis of Stages I and II, a false discovery rate approach was applied. Among the 14 candidate SNPs, eight showed significant association (combined P < 0.01) with the occurrence of HP. The SNPs rs4709583 (PARK2) and rs10476823 (HDAC3) were analyzed for potential functional effects on RNA splicing and RNA half-life. Despite its location near a splice site, alternative splicing was not detected for rs4709583 (PARK3). By contrast, cDNA analysis revealed use of a cryptic polyadenylation signal in the 3′UTR of HDAC3 mRNA and a longer mRNA half-life in a cell line heterozygous for rs10476823. © 2014 Wiley Periodicals, Inc.